2016
DOI: 10.21037/tau.2016.04.04
|View full text |Cite
|
Sign up to set email alerts
|

A review of surgical strategies for penile prosthesis implantation in patients with Peyronie’s disease

Abstract: The introduction of the inflatable penile prosthesis (IPP) has revolutionized the treatment of patients with both Peyronie’s disease (PD) and erectile dysfunction (ED). A thorough literature review was performed in order to review the surgical strategies used to treat PD, using the PubMed online database with the keywords “penile prosthesis”, “surgical management” and “Peyronie’s disease”. Patient satisfaction rates of 72–100% and partner satisfaction rates of 89% have been reported in the literature, although… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(10 citation statements)
references
References 80 publications
(158 reference statements)
0
9
0
1
Order By: Relevance
“…16,21,23À28 PP þ Plication If there is persistence of a 30À40 degree curvature after MM in a patient with adequate penile length and no hour-glass deformity, then plication can be attempted to improve the residual curvature. 29 Nesbit's plication involved excising a strip of the plaque containing tunica albuginea and subsequent reapproximation of the tunical edges, whereas the less invasive Essed-Schroeder technique involved plication without any tunical incision. 30 The 16/24-dot technique is a modification of Essed-Schroeder plication involving application of 2 (16 dots) or 3 (24 dots) pairs of plications depending on the degree of curvature.…”
Section: Technique Of MMmentioning
confidence: 99%
See 1 more Smart Citation
“…16,21,23À28 PP þ Plication If there is persistence of a 30À40 degree curvature after MM in a patient with adequate penile length and no hour-glass deformity, then plication can be attempted to improve the residual curvature. 29 Nesbit's plication involved excising a strip of the plaque containing tunica albuginea and subsequent reapproximation of the tunical edges, whereas the less invasive Essed-Schroeder technique involved plication without any tunical incision. 30 The 16/24-dot technique is a modification of Essed-Schroeder plication involving application of 2 (16 dots) or 3 (24 dots) pairs of plications depending on the degree of curvature.…”
Section: Technique Of MMmentioning
confidence: 99%
“…33 To prevent cylinder herniation or curvature recurrence due to scar contracture, grafting is usually recommended when the tunical incisional defect is larger than 2 cm. 29 There are 3 approaches: i) combined peno-scrotal incision for PP placement and degloving circumcoronal penile incision for plication or grafting; ii) circumcoronal penile degloving incision alone; or iii) penoscrotal incision with the penile inversion technique.…”
Section: Pp þ Incision /Excision Of Plaque With Graftsmentioning
confidence: 99%
“…Loss of penile length has been reported in 54% of patients postoperatively and is one of the primary concerns of patients. 16 Maximal sizing and postoperative rehabilitation with inflatable PP implantation have been recommended to prevent the loss of penile length in patients with severe ED unrelated to PD. 17 18 Recent studies have demonstrated that the ST is an effective method to not only perform PP implantation but also restore length in patients with severe PD and ED.…”
Section: Commentmentioning
confidence: 99%
“…17,18 Recent studies have demonstrated that the ST is an effective method to not only perform PP implantation but also restore length in patients with severe PD and ED. 6,7,16,19 Rolle et al 7 conducted a multicentric study on the outcomes of the ST with complete degloving of the penile shaft in 28 patients. The ST demonstrated an intraoperative straightening of all penises, an average increase of 3.2 cm in penile length, and an overall increase in patient satisfaction rate at the expense of a slight increase in complications.…”
Section: Commentmentioning
confidence: 99%